Emotional Intelligence and Perceived Stress Among Postgraduate Engineering Students: A Cross-Sectional Study - Banu, P.; Rani, S. (Journal of Engineering Education Transformations, 2025)
Emotional intelligence (EI) can be a critical tool for post-graduate engineering students, who frequently deal with high levels of workload and academic pressure. EI can be crucial in controlling perceived stress. The term "perceived stress" describes how people understand and respond to environmental pressures. Students possessing elevated emotional intelligence might find themselves more adept at managing the challenges in their personal and academic spheres. This capability could potentially mitigate stress levels while simultaneously improving academic success and overall welfare. This study aims to assess how EI correlates with the perceived stress levels among postgraduate engineering students. Using a convenience sample and a cross-sectional, descriptive correlational approach, 283 students aged 21 years and older were selected from Virudhunagar. Conventional self-administered surveys, "The Schutte Self-Report Emotional Intelligence Test (SEIT)" and "Perceived Stress Scale (PSS-14)," were used to measure EI and PS individually. Results indicates the relationship between managing one's own emotions and perceived stress was found to be negative and significant (β = -0.033, t = 2.199, p = 0.028). Managing other emotions showed a substantial positive and significant linkage with perceived stress (β = 0.404, t = 15.170, p < 0.001). Perceptions of emotion demonstrated a potent positive and significant correlation with perceived stress (β = 0.700, t = 26.903, p< 0.001). Utilization of emotions was negligibly related to perceived stress (β = 0.005, t = 0.251, p = 0.802). These findings suggest that while self-regulation helps alleviate stress, heightened interpersonal emotional management may contribute to stress among postgraduate engineering students